„Ach, bal więc bal!" - polifoniczność dialogu w Za kulisami Norwida i Operetce Gombrowicza - Jarząbek, Dorota (Przestrzenie Teorii, 2007)
The article presents some reflections on a dramatic motive of a bali (including a masked bali) in Polish 19,h and 20,h century drama, and tightly connected with this a problem of a polilogue (dialogue of a group of people as opposed to an ordinary dialogue with two persons involved). A masked bali in a drama gives an opportunity to show various ways of concealing and creating one's personality. It may be used as a sharp satirical cabaret, a grotesque composition on the edge of reality and dream (Za kulisami) or a kind of metaphor for processes of a human History (Operetka). Ali the cases are based on a fruitful use of a polilogue. It enables a playwright to intensify dramatic action, to give the show some scenic shine and colours, and also to penetrate into the question of characters' ontology: their existence in the polyphonic dialogue as a real being or a sketch, a sign of a person, a chorus or simply a background.